2020
DOI: 10.3390/ma13112520
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Rheological, and Morphological Properties of Asphalt Reinforced by Basalt Fiber and Lignin Fiber

Abstract: Studies show that each kind of fiber has its own advantages in improving the properties of asphalt binders. However, there are very limited research studies about mixed fiber-reinforced asphalt (MFRA). In this study, two kinds of fibers, basalt fiber (BF) and lignin fiber (LF), were selected to reinforce SBS (styrene–butadiene–styrene triblock copolymer)-modified asphalt, which is now widely used in pavement engineering. MFRA samples with different fiber mix ratios (FMRs) were prepared for the tests of softeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 27 publications
0
21
0
2
Order By: Relevance
“…Different fibers have different characteristics, for instance, plant fibers usually have less strength than mineral fibers. The fracture strength of lignin fibers (plant fiber) is smaller than basalt fibers (mineral fiber) [ 16 ], it could also degrade in the mixtures during long-term service. However, the plant fibers such as the lignin fiber could absorb the asphalt very well [ 17 , 18 ] in the mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Different fibers have different characteristics, for instance, plant fibers usually have less strength than mineral fibers. The fracture strength of lignin fibers (plant fiber) is smaller than basalt fibers (mineral fiber) [ 16 ], it could also degrade in the mixtures during long-term service. However, the plant fibers such as the lignin fiber could absorb the asphalt very well [ 17 , 18 ] in the mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing traffic loading has led to the exploration of high-performance asphalt binders. Several studies showed that modification of base asphalt binders enhances their physical and rheological properties, resulting in minimizing common types of distresses, such as fatigue, low-temperature cracking, and rutting deformation, encountered in asphalt pavements [ 1 , 2 , 3 , 4 ]. Recently, nanomaterials, due to their high functional density, high specific surface area, and strong absorption, have demonstrated a great potential to improve the properties of the binder, leading to high performance and prolonged service life of the pavement [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [27] evaluated the enhancement impact of SBS and basalt fiber on anti-rutting and anti-cracking of modified asphalt mixture by the Hamburg wheel track test and the low temperature bending test, respectively. Kou et al [28] selected basalt fiber to reinforce asphalt materials incorporating of SBS polymer, and they found that asphalt materials incorporating of SBS polymer and basalt fiber can make use of both advantages of additives [29][30][31]. Badeli et al [32] explored the influences of F-T actions on fatigue cracking of asphalt mixtures considering seasonal ambient temperature variations.…”
Section: Introductionmentioning
confidence: 99%